Effect of coupled channels of the multi-channel pion-pion scattering in two-pion transitions of the Y mesons; International Journal of Modern Physics: Conference Series; Vol. 39 : The 9th Joint International Hadron Structure '15 Conference, Horný Smokovec, Slovak Republic, 29 June-3 July 2015 - Surovtsev Yu. S. Yury Stepanovich; Bydzovsky P.; Gutsche Th. Thomas; Kaminski R. Robert; Nagy M. Miroslav; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich (2015, 2015)
Title screen